2018
DOI: 10.1016/j.immuni.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

T Follicular Helper Cell-Germinal Center B Cell Interaction Strength Regulates Entry into Plasma Cell or Recycling Germinal Center Cell Fate

Abstract: Higher- or lower-affinity germinal center (GC) B cells are directed either to plasma cell or GC recycling, respectively; however, how commitment to the plasma cell fate takes place is unclear. We found that a population of light zone (LZ) GC cells, Bcl6CD69 expressing a transcription factor IRF4 and higher-affinity B cell receptors (BCRs) or Bcl6CD69 with lower-affinity BCRs, favored the plasma cell or recycling GC cell fate, respectively. Mechanistically, CD40 acted as a dose-dependent regulator for Bcl6CD69 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
284
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(301 citation statements)
references
References 54 publications
17
284
0
Order By: Relevance
“…Overall, our findings are consistent with the previously discovered role of Ag-dependent BCR engagement in driving GC differentiation into PB. However, although in the previous study, T cell help has been shown to be critical for maturation and survival of the early GCPB (Kräutler et al, 2017), our findings are more consistent with another study (Ise et al, 2018) and suggest that an ongoing T cell help is required, even for the initial differentiation of GC B cells into PBs.…”
Section: Resultssupporting
confidence: 86%
“…Overall, our findings are consistent with the previously discovered role of Ag-dependent BCR engagement in driving GC differentiation into PB. However, although in the previous study, T cell help has been shown to be critical for maturation and survival of the early GCPB (Kräutler et al, 2017), our findings are more consistent with another study (Ise et al, 2018) and suggest that an ongoing T cell help is required, even for the initial differentiation of GC B cells into PBs.…”
Section: Resultssupporting
confidence: 86%
“…Smith et al first demonstrated by analyzing NP hapten-specific B-cell responses that the extent of affinity maturation differs between plasma cells and memory B cells. 25,27 Hence, the fate of GC B cells is highly correlated with their BCR affinity, and the high-affinity cells tend to be selected into the plasma cell pool. 23 .…”
Section: Pl a S Ma Cell S Elec Ti On During The G C Re Ac Ti Onmentioning
confidence: 99%
“…[36][37][38] In this system, extrinsic antigen is delivered to GC B cells via the C-type lectin endocytic receptor DEC205 (CD205), instead of via the BCR, and presentation of processed antigen peptide facilitates the interaction Krautler et al has recently suggested that the CD40 signal is dispensable for the generation of early plasma cells by using a CD40L blocking mAb in HEL-SRBC immunized mice. 27 Foxo1. 27 Foxo1.…”
Section: S I G Nal S That Induce G C B Cell S To B Ecome Pl a S Ma mentioning
confidence: 99%
See 1 more Smart Citation
“…98 Expression of IRF4 is important for the formation and function of GCs. Recent studies have suggested that high-affinity B cells in the light zone receive strong CD40 signals, downregulate BCL6, and exit the GC reaction as IRF4 + CD69 + cells that eventually differentiate into plasmablasts.…”
Section: Plasma Cellsmentioning
confidence: 99%